Finite element modeling and simulation of rail steel track loading - Beh, Ruey Yan (2018)
This project evaluated the behaviours of the rail track components under static loading conditions. Rail track finite element models were created by using three-dimensional finite element analysis software (FEA) ABAQUS. The objective of these models is to investigate the stresses distribution and deformation on the rail track components. Furthermore, the effect of vertical and lateral loads on the contact stress and contact area were reviewed in this report. Firstly, the study began with a simple straight track model to analyse the impact of vertical loads on the contact stresses at the wheel-rail interface. The results obtained from ABAQUS were used to compare the analytical solution based on Hertz contact theory. The difference between maximum contact pressure and the contact area between FEA and analytical method were evaluated. The results show the deviation of contact pressure between analytical method and finite element models were relatively small. The study was extended to analyse the stress distribution on the elevated curved rail track. The lateral forces acting on rail vehicle applied in these curved track model simulations. The comparison was made with the straight track and differences were analysed. The effect of lateral forces on the contact stress and contact position were investigated in detail. The contact stress and position changed obviously when the lateral-to-vertical load ratio raised to 0.5.